Response of Nafion to Contact with Ketone Like Substances - Orozco Alvarado, Ing. Miguel Alonso; Navarro Torres, Nancy Janeth; Lucero, Alfredo Marquez (Current Topics and Emerging Issues in Materials Sciences Vol. 1, 2023)
Nafion is a sulfonated tetrafluoroethylene-based fluoropolymer-copolymer, which is an excellent material for fuel cell membranes. This widely used copolymer has been investigated for decades, but it has been hardly considered as a sensitive layer to organic vapours, but only as a conductor of electricity. However, its sensitive properties make it an interesting material for sensor applications. Indeed, the mass production of this material open new developments to design reliable and cheap sensors, useful for military, industrial and medical applications. In this work, we study Nafion (and eventually other ionomers) physical and transport response when it enters in contact with ketone vapours, on the perspective to design new chemical sensors, more compact and cheaper. This work shows the possibility to employ sulfonated tetrafluoroethylene-based fluoropolymer-copolymer, commercially known as Nafion, as a sensible layer on sensors to detect organic solvents such as ketones. The detection and evaluation of ketone corpuses is very important for multiple applications on medicine, specially to detect and evaluate Diabetes Mellitus from the breath of patients. Nafion is a very stable copolymer, easily available and relatively inexpensive. This allows us to envision the possibility of having cheap and reliable sensors to detect vapours of these substances based on this copolymer. The main result of the present work is that; Nafion can protonate gaseous ions from organic solvents, such as acetone and similar substances, which modify its electrical properties, presenting a differentiated behavior according to the chemical nature of these substances, which could lead to their identification, designing an electrical nose, because each behaviour is a fingerprint of the substance to detect. Then this material can be used in the design of electrical sensors, which can be low-cost, reliable, and chemically stable, representing an excellent alternative to ceramic sensors.